VIRTUAL OBJECTS FOR TEACHING AND LEARNING IN MATHEMATICS TEACHING: SIMULATE, ANALYZE ROUTES AND DISTANCES WITH GOOGLE MY MAPSSIMULATE, ANALYZE ROUTES AND DISTANCES WITH GOOGLE MY MAPS - Adeilton de Oliveira Andrade, Emanuel; Maria da Silva Moura, Hélio; dos Santos Borges, Jassiara (Journal of Interdisciplinary Debates, 2023)
this activity aimed to investigate how the 6th year students of the monsenhor walfredo gurgel municipal school in the city of alto do rodrigues-rn, interpret mathematics in urban routes and aerial views. for the development of activities we use google maps to simulate and analyze routes and distances. the proposed simulations aimed at simulating and analyzing urban routes, building maps and geometric figures, with virtual learning objects (ova’s), providing students with learning that used their mathematical knowledge and digital technologies to validate strategies and solve everyday problems.